O luto em Freud e suas articulações com a temporalidade na cultura contemporânea - Ramos, Vitor Costa (Universidade Federal de São Carlos, 2026)
The purpose of this dissertation is to investigate mourning from a Freudian perspective, in articulation with contemporary culture, with a focus on the dimension of temporality. This is a theoretical study grounded in psychoanalytic theory. The first chapter addresses the status of mourning in Freud, discussing its metapsychology, the notion of the work of mourning, its main clinical signs, and the question of its termination. The second chapter examines the effects elicited by loss, particularly in the intrapsychic domain and its clinical developments, considering different modes of reaction to object loss that may hinder or prevent the accomplishment of the work of mourning. The third and final chapter proposes an articulation between mourning, temporality, and contemporary culture, prioritizing the relationship between the mourning subject and time. From this perspective, it is understood that the task of mourning takes place at the intersection of the individual and the collective, articulating intrapsychic, intersubjective, and social dimensions. It is observed that the temporality of mourning, which is explicitly subjective, appears antagonistic to the prevailing modes of relating to time in contemporary culture, marked by speed and urgency. The hypothesis advanced is that, in the present context, there is a temporal impasse between the accelerated time promoted by culture and the subject’s subjective temporality. Thus, the time offered to the subject may function as an obstacle to the temporal movement required by mourning, hindering the work of working-through and symbolization in the face of loss.
Grief in Freud and its connections to temporality in contemporary culture
Keywords: Luto; Psicanálise; Temporalidade; Cultura contemporânea; Freud; Grief; Psychoanalysis; Temporality; Contemporary culture; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar